2005
DOI: 10.1128/jcm.43.4.1581-1586.2005
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification Method Targeting the lytA Gene for Detection of Streptococcus pneumoniae

Abstract: It is difficult to separate Streptococcus pneumoniae from the genotypically similar species Streptococcus mitis and Streptococcus oralis, which are commensals of the human oral cavity. A novel nucleic acid amplification technique, loop-mediated isothermal amplification (LAMP), which amplifies DNA under isothermal conditions (63°C) with high specificity, efficiency, and rapidity, was examined regarding its applicability for detecting S. pneumoniae. An S. pneumoniae-specific LAMP primer targeting the lytA gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 23 publications
7
72
2
Order By: Relevance
“…The F2 and B2 primers were used for PCR amplification of a portion of the LAMP product. 29 However, in this case, the PCR amplified LAMP product sequence was identical to the original Strongyloides sequence targeted by the LAMP primers, and not particular to the LAMP reaction. Analytical specificity and sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The F2 and B2 primers were used for PCR amplification of a portion of the LAMP product. 29 However, in this case, the PCR amplified LAMP product sequence was identical to the original Strongyloides sequence targeted by the LAMP primers, and not particular to the LAMP reaction. Analytical specificity and sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…This was based on PCR of the LAMP product using primers F2 and B2. 29 HotStarTaq DNA polymerase and PCR buffer (Qiagen) were used according to instructions from the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…High specificity is assured since target recognition is mediated by four distinct primers targeting six different sequences (Notami et al 2000;Nagamine et al 2002;Fukuta et al 2004). In some studies, LAMP was even shown to be more selective (Seki et al 2005) and less sensitive to background DNA (Notami et al 2000) than PCR. LAMP has high amplification efficiency and with a lower amount of sample DNA (1-10 ng) (Guan et al 2010, it yields DNA in quantities of more than 500 g/ml (Morriset et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Fakruddin, 2011). LAMP has also been broadly applied in pathogen detection, and has successfully detected Escherichia coli O157:H7 (Maruyama, Kenzaka, Yamaguchi, Tani, & Nasu, 2003), Actinobacillus actinomycetemcomitans (Osawa et al, 2007), Mycobacterium tuberculosis (Iwamoto, Sonobe, & Hayashi, 2003), Streptococcus pneumonia (Seki et al, 2005), and Listeria monocytogenes (Tang et al, 2011). More recently, LAMP has been used to successfully detect S. aureus (Lim, Ju Teh, & Thong, 2013).…”
Section: Introductionmentioning
confidence: 99%